Strategi Revitalisasi Kantor Urusan Agama Kecamatan Mundu dan Kedawung Kabupaten Cirebon - Saogi, Achmad (JURNAL ILMIAH GEMA PERENCANA, 2022)
The revitalization of the Sub-district KUA Religious Affairs Office is a priority program of the Minister of Religious Affairs of the Republic of Indonesia. The Cirebon Regency Religious Affairs Ministry office is required to implement the program. A strategy is needed to implement it so that the sub-district Office of Religious Affairs revitalization program in Cirebon Regency is running. The method in this article uses descriptive qualitative, namely direct observation and interviews with relevant stakeholders. There are three elements of strategy according to Richard P. Rumelt, namely diagnosis, guiding policies and coherent actions. The diagnosis found obstacles in the form of institutional infrastructure, material infrastructure, and personal infrastructure. Other problems are lack of cooperation between employees, lack of budget, location of KUA is also less strategic, and information services are not optimal. In the guiding policy a thorough evaluation is made in order to identify existing weaknesses, complaint services are strengthened, coordination is carried out internally and externally. Mapping of employees and revision of the existing budget. The coherent actions taken were through meetings, coordination and reviewing the existing and revised budgets. The Ministry of Religion office must strengthen coordination and evaluation and maximize its services.